A Narrative Analysis of the Influence of Metacognitive Skills and Self-Efficacy on Chemistry Learning Achievement among Students - Ilham Assidiq; Sitti Mania; Yuspiani Yuspiani; Usman Usman (Yayasan Adra Karima Hubbi, 2026)
Background. Chemistry learning is influenced by various psychological factors, including students’ metacognitive skills and self-efficacy. Both factors play a crucial role in motivating students to learn effectively. Therefore, it is essential for educators to understand how metacognitive skills and self-efficacy impact students’ performance in chemistry. Purpose. This study aims to investigate the impact of metacognitive skills and self-efficacy on chemistry learning achievement among students in Enrekang Regency. Additionally, this study examines the relationship between these psychological factors and how they contribute to the improvement of students’ chemistry performance. Method. Pearson product-moment correlation was used to assess the strength and direction of associations between the study variables, while multiple linear regression analysis was conducted to evaluate the extent to which metacognitive skills and self-efficacy jointly predict students’ chemistry learning achievement. The significance level for all statistical analyses was set at ? = 0.05. Results. The findings indicate that metacognitive skills and self-efficacy have a significant positive correlation with chemistry learning achievement. Specifically, self-efficacy has a stronger influence than metacognitive skills in predicting chemistry learning achievement. Regression results show that both factors can explain 36% of the variance in students’ chemistry learning achievement. Conclusion. This study contributes to the growing body of research on educational psychology by demonstrating the significance of self-efficacy and metacognitive skills in predicting chemistry learning achievement. The findings suggest that educators should incorporate instructional practices that promote students’ metacognitive regulation and strengthen their self-efficacy, as these factors may play a crucial role in improving learning outcomes and overall academic success in chemistry education.